REAKSI PASAR DI SEKITAR PENGUMUMAN EMPLOYEE STOCK OWNERSHIP PROGRAM PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Delcia Oktora; Amries Rusli Tanjung; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The relationship between management and owners of the company is the principal-agent relationship paradigm. And their interest can be different, which was called by the agency problems. For this case, Employee Stock Ownership Program (ESOP) have been created to increase or creating value of the firm and reducing the agency problem. The purpose of this research was to know how the market reaction around the announcement of ESOP and to analyze the difference of market reaction on high growth potential companies and low growth potential companies in January1, 2010 – December 31, 2013. The sampling is selected using purposive sampling on secondary data from financial reports that are available in the Indonesia Stock Exchange Website. The method of analysis for analyzing the market reaction around the announcement of ESOP used one sample t-test and analyze the difference of market reaction on high growth potential companies and low growth potential companies used independent sample t-test. The results of this research showed that there was the positive market reaction around the announcement of ESOP during event window and for market reaction on high growth potential companies and low growth potential companies, there are significant differences in market reaction around the announcement, where the market is likely to react positively to high growth potential companies than low growth potential companies.Keywords: Employee Stock Ownership Program (ESOP), Market Reaction